What is architectural history? - Leach, Andrew (Cambridge, UK : Polity Press, 2010)
'How do historians of architecture organize past time and relate it to the present? How does historical evidence translate into historical narrative? Should architectural history be useful for practising architects? If so, how? Leach treats the disciplinarity of architectural history as an open question, moving between three key claims upon historical knowledge of architecture: within art history, as a historical specialization and, most prominently, within architecture.'--Back cover.
Includes bibliographical references (p. [156]-163) and index.
Keywords: Architecture -- Historiography